New optical near-field nanolithography with optical fiber probe laser irradiating atomic force microscopy probe tip. Issue 169 (12th February 2016) - Cui, Jianlei; Yang, Lijun; Xie, Hui; Wang, Yang; Mei, Xuesong; Wang, Kedian; Wang, Wenjun; Hou, Chaojian
ABSTRACT: A new optical near-field nanolithography scheme with optical fiber probe laser irradiating atomic force microscopy (AFM) probe tip is proposed. Through optical theoretical analysis, if the metallic AFM probe tip is in the evanescent field of optical fiber probe tip, the secondary near-field enhancement effect can appear underneath the metallic AFM probe tip. Based on the independently developed AFM system and optical system, the nanolithography platform is built and nanocraters structures can be successfully created, which demonstrates that the new scheme is an effective and promising nanolithography approach for the future nanoelectronics, nanobiotechnology, nanowelding, etc.